Implementasi Algoritma Camellia Pada Penyandian Citra USG - Fara Dibba Mutiara Maharani (Journal of Information System Research (JOSH), 2020)
Digital images are very vulnerable to data capture or theft by irresponsible parties. For the sake of maintaining the security of USG images can be done by using cryptographic techniques. Cryptographic techniques can encode ultrasound images by encrypting them in the form of codes that are not understood. Camellia Algorithm is one algorithm that can be relied upon to realize cryptographic techniques. This symmetry algorithm will produce a higher level of security to the USG image because it can encode it into a cipher with a process that is complex enough so that it will be difficult for cryptanalysts to access the image. This research will use the 128-bit Camellia Algorithm for the encryption and decryption process, so the process needs to go through several long stages in order to produce the final cipher. This algorithm requires 18 rounds where every six rounds must enter Function F and FL-1 Functions and also requires as many as 26 subkeys namely kw, k and kl. This study describes the process of securing the USG image by encoding it based on the Camellia algorithm, in the form of a password that is difficult for others to understand and understand. This is done as an effort to minimize acts of misuse of the USG image.